Peran Pamong Belajar: Studi Naturalistik terhadap Pamong Belajar dalam Melaksanakan Layanan Program Pendidikan Non Formal - Sri Wahyuni (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2021)
Research purpose for: 1)Describe the role of tutors in implementing nonformal education programs, 2)Describe the tutors education qualifications, 3) Identify the tutors obstacles in carrying out their duties and functions. The type of research used is qualitative naturalistic research. The research subjects were tutors and leader of the Center for Early Childhood Education Development and Community Education in East Kalimantan Province. Data collection techniques used observation, interview,and documentation studies. The data analysis technique used is the interactive model analysis of Miles and Huberman namely data reduction, data display, and verification. The research results: 1)The role of tutors in providing nonformal education service can be seen from their exsistence in carrying out their duties and functions, namely as educators, program reviewers, and model developers. The tutors education qualifications are in accordance with the minimum standard of academic qualifications, namely undergraduate and postgraduate. 3)The obstacles for tutors are: a)Inadequate facilities and infrastructure to carry out the duties and functions of the institution, b)The head of the center has not provided maximum direction regarding the duties and functions of the tutors, c)Proposing a credit score for tutors is difficult, d)Lack of equal opportunities for tutors to be involved in various activities.